2022
DOI: 10.2337/db22-0315
|View full text |Cite
|
Sign up to set email alerts
|

Fat Distribution Patterns and Future Type 2 Diabetes

Abstract: Fat accumulation in the liver, pancreas, skeletal muscle, and visceral bed relates to type-2 diabetes (T2D). However, the distribution of fat among these compartments is heterogenous and it is unclear whether specific distribution patterns indicate high T2D risk. We therefore investigated fat-distribution patterns and their link to future T2D. From 2168 individuals without diabetes who underwent computed tomography in Japan, this case-cohort study included 658 randomly selected individuals and 146 incident cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Lower body fat content is generally considered metabolically beneficial; however, the storage of triglyceride safely in WAT is also an important aspect of metabolic health [ 70 ]. Our previous work shows that uncontrolled adipose lipolysis stimulated by high circulating hepatic Fst in LDKO mice potentiates hepatic gluconeogenesis and diabetes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower body fat content is generally considered metabolically beneficial; however, the storage of triglyceride safely in WAT is also an important aspect of metabolic health [ 70 ]. Our previous work shows that uncontrolled adipose lipolysis stimulated by high circulating hepatic Fst in LDKO mice potentiates hepatic gluconeogenesis and diabetes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predictions of this hypothesis were subsequently confirmed in interventional studies of a low-energy diet: the Counterpoint, Counterbalance and DiRECT trials [ 37 39 ]. Further, a 2022 data-driven cluster analysis partitioned individuals without diabetes based on their abdominal fat distribution and then studied the longitudinal association of membership in the resulting clusters with incident type 2 diabetes [ 40 ]. The study showed that individuals with excess liver fat and those with excess IPFD (but not those with excess skeletal muscle fat deposition) are at remarkably similar (fourfold and 3.4-fold higher, respectively) risk of type 2 diabetes, further supporting the link between liver fat and IPFD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a 2022 data-driven cluster analysis partitioned individuals without diabetes based on their abdominal fat distribution and then studied the longitudinal association of membership in the resulting clusters with incident type 2 diabetes [ 40 ]. The study showed that individuals with excess liver fat and those with excess IPFD (but not those with excess skeletal muscle fat deposition) are at remarkably similar (fourfold and 3.4-fold higher, respectively) risk of type 2 diabetes, further supporting the link between liver fat and IPFD [ 40 ]. The use of the path-analytic methodological framework and the large sample size of the present observational study enabled us to provide robust complementary evidence that supports the interconnectedness of IPFD and liver fat.…”
Section: Discussionmentioning
confidence: 99%
“…The lower-body region is one of the major areas for the accumulation of subcutaneous adipose tissue. Different adipose depositions have been recognized to cause different metabolic consequences ( 9 , 10 ). Those who accumulate fat tissue in the trunk region (android obese) are more likely to develop diabetes and cardiovascular diseases (CVDs) than those with major lower-body-fat mass (LFM) deposition (gynoid obese) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different adipose depositions have been recognized to cause different metabolic consequences ( 9 , 10 ). Those who accumulate fat tissue in the trunk region (android obese) are more likely to develop diabetes and cardiovascular diseases (CVDs) than those with major lower-body-fat mass (LFM) deposition (gynoid obese) ( 10 ). One of the reasons for the higher prevalence of CVDs in men than in women is that men tend to develop android obesity, whereas women tend to develop gynoid obesity ( 11 ).…”
Section: Introductionmentioning
confidence: 99%